2011
DOI: 10.1089/jwh.2010.2139
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Sexually Transmitted Infection Underreporting Among Female Sex Workers in China

Abstract: Objective: To examine the underreporting of sexually transmitted infections (STI) (i.e., no STI by self-report but have at least one STI through biological testing or clinical examination) and factors associated with underreporting among female sex workers (FSWs) in China. Methods: A total of 454 FSWs were recruited from entertainment establishments in a rural county of Guangxi, China. Participants completed a self-administered survey about their demographic and working characteristics, history of STI (past or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 26 publications
5
20
1
Order By: Relevance
“…Indeed, the majority of females who worked in entertainment venues were more likely to earn more than 1500 Yuan monthly than females worked in factory and restaurants, indicating the possible influence of financial motivations in migrants' decisions to work in entertainment venues . Findings reported here are also consistent with other studies indicating that females working in entertainment venues are likely to have multiple sexual partners Chen et al, 2011;Hong et al, 2011). Findings are consistent with results reported by Yang et al (Yang et al, 2005), who found that females working in entertainment establishments in China engaged in risky sexual practices twice as frequently as females working in non-entertainment establishments.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, the majority of females who worked in entertainment venues were more likely to earn more than 1500 Yuan monthly than females worked in factory and restaurants, indicating the possible influence of financial motivations in migrants' decisions to work in entertainment venues . Findings reported here are also consistent with other studies indicating that females working in entertainment venues are likely to have multiple sexual partners Chen et al, 2011;Hong et al, 2011). Findings are consistent with results reported by Yang et al (Yang et al, 2005), who found that females working in entertainment establishments in China engaged in risky sexual practices twice as frequently as females working in non-entertainment establishments.…”
Section: Discussionsupporting
confidence: 93%
“…While these fractions are higher than several previous studies that have considered prior STI infection status and number of sexual partners among Chinese participants [12], [36], [37], studies in other countries have noted similar percentages [38]. Neither of these factors was associated with an increased risk of infection with reduced susceptibility to ceftriaxone or resistance to penicillin or tetracycline in this study.…”
Section: Discussioncontrasting
confidence: 82%
“…In a recent cross-sectional study, we found no positive associations between self-reported gCT or pelvic inflammatory disease and fibroids; in fact, women reporting a history of gCT tended to have fewer and smaller fibroids (13). These previous studies measured gCT history with self-reported questionnaire data, which can be plagued by recall error and misclassification due to the asymptomatic nature of gCT (14)(15)(16)(17). A serological measure of exposure, identifying antibodies in the serum that remain after infection, would provide more accurate exposure assessment than self-reported gCT.…”
mentioning
confidence: 66%